ODONTOGENIC INFECTIONS AND CARDIORESPIRATORY COMPLICATIONS - de Oliveira Reckel, Leandro; Bergamo, Douglas; Piona Silvestrini Bergamo , Lays; Miranda Conceição, Gabriel; de Brito Véras, Wagner (UNESC em Revista, 2025)
Odontogenic infections are common conditions in clinical dental practice, originating from inflammation of dental and periodontal tissues, with the potential to spread to adjacent structures and cause systemic infections. Among systemic complications, those affecting the cardiorespiratory system are particularly relevant, ranging from infective endocarditis to lung abscesses. The present study seeks to understand the relationship between these infections and systemic complications, especially those that affect the cardiovascular system and infections, contribute to the prevention, diagnosis and treatment of these conditions. A literature review was carried out in the Scielo, PubMed and Google Scholar databases to contribute to the process of systematizing and analyzing the results of other publications, with the aim of understanding the topic through independent studies. The results highlight a significant manifestation between odontogenic infections and complications in the cardiorespiratory system. Odontogenic infections are directly associated with cardiorespiratory complications, which reinforces the importance of a preventive approach and early diagnosis